Historical Insight into Infections and Disorders Associated with Neurological and Psychiatric Sequelae Similar to Long COVID - Stefano, George B (Medical science monitor, 2021)
Long-term sequelae of coronavirus disease 2019 (COVID-19) due to infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are now recognized. However, there is still a lack of consensus regarding the terminology for this emerging chronic clinical syndrome, which includes long COVID, chronic COVID syndrome, post-COVID-19 syndrome, post-acute COVID-19, and long-hauler COVID-19. In this review, I will use the term "long COVID". A review of the medical history and epidemiology of past pandemics and epidemics in modern literature review identifies common long-term post-infectious disorders, with the common finding of altered cognition. In the brain, the cerebral hypoxia induced by SARS-CoV-2 infection may be caused by mitochondrial dysfunction, resulting in "brain fog". Historically, the common symptom of altered cognition has been reported during earlier pandemics, which include the influenza pandemics of 1889 and 1892 (Russian flu), the Spanish flu pandemic (1918-1919), encephalitis lethargica, diphtheria, and myalgic encephalomyelitis (chronic fatigue syndrome or post-viral fatigue syndrome). There are similarities between chronic fatigue syndrome and the "brain fog" described in long COVID. During past viral epidemics and pandemics, a commonality of neural targets may have increased viral survival by conformational matching. The neurological and psychiatric sequelae of SARS-CoV-2 infection, or long COVID, may have emerged from neural effects that have emerged from an invertebrate and vertebrate virosphere. This review aims to present a historical overview of infections and disorders associated with neurological and psychiatric sequelae that have shown similarities with long COVID.
Keywords: Post-Acute COVID-19 Syndrome; kognitivní dysfunkce; mozek; Influenza Pandemic, 1918-1919; pandemie španělské chřipky 1918-1919; Pandemics; lidé; postakutní syndrom COVID-19; Brain; pandemie; History, 21st Century; dějiny 21. století; Humans; Cognitive Dysfunction; COVID-19; SARS-CoV-2